Evaluasi Sistem Informasi Manajemen Puskesmas (SIMPUS) dengan Pendekatan HOT-Fit Model di Puskesmas Baturraden II - Bella, Cindy Rozza; Ummah, Shofiatul; Isnaeni, Rizka (Lembaga Penerbitan Universitas Esa Unggul, 2025)
SIMPUS is an application designed to manage public health centers (Puskesmas), specifically created to handle patient data from registration to report generation. Generally, the implementation of SIMPUS in Baturraden II Public Health Center has AbstractSIMPUS is an integrated information system that supports service management in Community Health Centers (Puskesmas), covering processes from registration to reporting. At Baturraden II Community Health Center, the system has been generally implemented; however, outpatient services still face efficiency challenges due to technical and operational issues. This study aims to evaluate the effectiveness of SIMPUS using a descriptive quantitative approach and the Human, Organization, Technology–Fit (HOT-FIT) framework. A total of 20 healthcare workers participated as the sample in data collection conducted in December 2023. The evaluation covered human aspects (competence, acceptance, satisfaction), organizational aspects (policies, leadership support, and support from the Health Office), and technological aspects (system development, system quality, and service quality). The findings indicate that although SIMPUS has been utilized for documentation and reporting, obstacles such as reliance on external servers and unstable internet connections still hinder smooth service delivery. Periodic evaluations are needed to improve system integration and service efficiency at the Community Health Center.Keyword: evaluation, SIMPUS, HOT-FIT modelAbstrakSIMPUS merupakan sistem informasi terintegrasi yang mendukung pengelolaan layanan di Puskesmas, mulai dari pendaftaran hingga pelaporan. Di Puskesmas Baturraden II, sistem ini telah diimplementasikan secara umum, namun pelaksanaan layanan rawat jalan masih menghadapi kendala efisiensi akibat gangguan teknis dan operasional. Penelitian ini bertujuan untuk mengevaluasi efektivitas SIMPUS dengan pendekatan kuantitatif deskriptif menggunakan kerangka kerja Human, Organization, Technology–Fit (HOT-FIT). Sebanyak 20 tenaga kesehatan dilibatkan sebagai total sampel dalam pengumpulan data yang dilakukan pada Desember 2023. Evaluasi mencakup aspek manusia (kompetensi, penerimaan, kepuasan), organisasi (kebijakan, dukungan pimpinan dan Dinas Kesehatan), serta teknologi (pengembangan, mutu sistem, dan kualitas layanan). Hasil penelitian menunjukkan bahwa meskipun SIMPUS telah digunakan untuk pencatatan dan pelaporan, masih ditemukan hambatan seperti ketergantungan terhadap server eksternal dan koneksi internet yang tidak stabil, yang berdampak pada kelancaran pelayanan. Diperlukan evaluasi berkala guna meningkatkan integrasi sistem dan efisiensi layanan di Puskesmas.Kata Kunci: evaluasi, SIMPUS, model HOT-FIT